A multidisciplinary clinic for pediatric patients with problematic severe asthma: Impact on clinical outcomes and healthcare utilization. Issue 3 (3rd July 2019) - Kam, Karen; Nettel-Aguirre, Alberto; Mitchell, Ian; Johnson, David W.; Currie, Gillian
Abstract: BACKGROUND: The Intensive Management of Asthma Clinic (IMAC) is a novel multidisciplinary clinic for children with problematic severe asthma. Whether consolidating resources in this clinic is effective in improving clinical outcomes and reducing unscheduled healthcare visits has not been studied. METHODS: This retrospective, observational cohort study compared the IMAC and regular asthma clinic at a pediatric quaternary care hospital over a 4-year period. Clinical outcomes (forced expiratory volume in 1 second [FEV1 ], number of oral steroid days, and short-acting beta-agonist [SABA] refills), and healthcare utilization and its costs (number of clinic visits, emergency department [ED] visits, hospitalizations) were collected. Linear mixed effects modeling was used to account for repeated measurements grouped into 3-month time intervals. RESULTS: Mean FEV1 was higher for IMAC patients by 4.6 (CI 1.1 to 8.1, p = 0.01) throughout the study period. Scheduled clinic visits were higher by 0.2 (CI 0.1 to 0.3, p < 0.01) on average in any 3-month time interval, while ED visits decreased by 0.1 (CI −0.2 to −0.1, p < 0.01) over time for the IMAC group. Hospitalizations decreased over time by 0.03 (CI −0.05 to −0.02, p < 0.01) for both groups. The increased cost of the IMAC was greater than total costs saved by subsequent decreased healthcare utilization. CONCLUSION: The increase in planned clinic visits for the IMAC group was associated with fewer unplanned ED visits. A multidisciplinary clinic for children with severe asthma can lead to decreased acute care utilization; however, these benefits may come at extra cost. Studies such as this enable decision-makers to judge whether the benefits of multidisciplinary clinics are worth the additional resources required.